LC-MS-MS and GC-MS analyses of biologically active extracts and fractions from Tunisian Juniperus phoenice leaves - Henda Keskes; Sahla Belhadj; Lobna Jlail; Abdelfattah El Feki; Mohamed Damak; Sami Sayadi; Noureddine Allouche (Taylor & Francis Group, 2017)
Context: Despite some studies related to Juniperus phoenicea L. (Cupressaceae), phytochemical and biological investigations of this plant remain unexplored. Objective: This work is the first report dealing with the identification and characterization of volatile components and flavonoids in hexane and methanol extracts from J. phoenicea leaves Materials and methods: Antioxidant activity of hexane, and methanol extracts from J. phoenicea leaves were determined by DPPH-radical scavenging assay. α-Amylase inhibitory activity was evaluated by enzyme inhibition using in vitro assay (each extract was dissolved in DMSO to give concentrations of 50, 100 and 200 mg/mL). The chemical composition of fractions (Fr1-Fr3) from methanol extract was determined by high-performance liquid chromatography coupled with mass spectroscopy (HPLC-MS) analysis. Results and discussion: The hexane extract was analyzed by GC-MS technique which allowed the identification of 32 compounds. The main constituents were α-humulene (16.9%), pentadecane (10.2%) and α-cubebene (9.7%). Fraction Fr 2 exhibited a strong DPPH radical-scavenging activity (IC50 = 20.1 μg/mL) compared to that of BHT as well as the highest α-amylase inhibitory activity (IC50 = 28.4 μg/mL). Three flavonoids were identified in these fractions using HPLC-MS analysis: Quercetin 3-O-glucoside, isoscutellarein 7-O-pentoside and quercetin 3-O-pentoside. In addition, the more active fraction (Fr 2) was purified with semi-preparative HPLC affording one pure compound (amentoflavone) using 1H NMR analysis. This compound exhibited powerful DPPH radical-scavenging (IC50 = 14.1 μg/mL) and α-amylase inhibition (IC50 = 20.4 μg/mL) effects. Conclusion: This study provides scientific support to some medicinal uses of J. phoenicea found in North Africa.